Movie Script-Based Learning: Best Practice to Improve Speaking Skills in EFL Classroom? - Ella Yuzar; Muntasir Muntasir; Fadhlur Rahman; Mohammad Kholid; Khairul Azmy (Journal of English Language Teaching, Linguistics, and Literature (JETLEE), 2026)
In communication, speaking acts as a productive skill that allows a person to convey ideas and meanings through voice articulation. In the context of English learning, it is important to find method/approach/technique that can stimulate students' interest in practicing speaking skills. Script from a movie offers advantages in improving speaking skills as they are able to capture students' attention and stimulate their curiosity. The aim of this paper is to assess the impact of employing movie scripts in the classroom to enhance students' speaking abilities. Fifty-eight English department students from a State Islamic University in Aceh participated in the study. They were divided into two groups: control (NUMS-None of Using Movie Script) and experimental (UMS-Using Movie Script). Prior to and subsequent to the treatment, they were screened. The students in the experimental group were assigned a task to create a video recording in groups of five characters from a movie at the conclusion of each meeting. They were also provided with a movie script and interactive instruction by the teachers. The results of the study suggest that there was a substantial difference between the pre-test and post-test. The mean difference of both post-tests was 65.9310 for the experimental group and 55.5862 for the control group. As the result, students' speaking ability improved after they learned how to use movie scripts properly, which enabled them to gain confidence, overcome the challenge of memorizing the script, easily organize ideas, and enrich their vocabulary stock. Accordingly, the mean score of the pre-test increased more than that of the post-test.